A study of the effect of measurement towards the enjoyment of using 360-degree video among tourist - Nur Anis Zulaikha, Ahmad (2023)
This study focuses on the effect of 360-degree video on enjoyment. The objective is to identify the measurement of information quality and examine its impact on enjoyment. The study proposes the effect of these measurements on the enjoyment of 360-degree video, particularly in the context of tourism in Malaysia. The measurements include novelty of content, reliability of content, understandability of content, and interest. The study incorporates the theory of planned behavior to enhance the understanding of how these measurements influence enjoyment. The research methodology involves several steps, including the creation of a 360-degree video and data collection. The research design encompasses the main study, the measurements, and the independent and dependent variables. Data analysis is conducted using Smart PLS 4. The questionnaire assesses the effect of the measurements on the enjoyment of 360-degree video, specifically novelty of content, reliability of content, understandability of content, and interest. The results indicate that users agree that these measurements contribute to the enjoyment of 360-degree video, and there is a significant positive relationship between these measurements and enjoyment. In conclusion, it is hoped that the findings of this study will encourage researchers and tourists to utilize 360-degree video as a means of promoting beautiful destinations worldwide.